Balanço de potássio no sistema solo-planta influenciado pela textura e adubação potássica em solos tropicais - Steiner, Fábio [UNESP] (2014)
Studies that include potassium budget (K) in the soil-plant system are important to assess whether the amounts of fertilizer applied annually are being harnessed to maintain and or improve soil fertility, or are intensifying K losses by leaching. The objective of this study was to evaluate the effect of potassium fertilization on the K budget in soil-plant system in two tropical soils with different textures. The experiments were carried out at the Experimental Farm Lageado in Botucatu, SP, 2000-2012, on a medium texture Oxisol (210 g kg–1 clay ) and other clay Oxisol (680 g kg–1 clay). Treatments consisted of seven levels of K applied annually (0, 30, 60, 90, 120, 150 and 180 kg ha–1 yr–1 K2O). Soil samples were collected at depths of 0–0.10; 0.10–0.20; 0.20–0.40; 0.40–0.60; 0.60–0.80 and 0.80–1.00 m in the twelfth year of the experiment. Potassium budget in the soil-plant system was calculated based on (i) amount of nutrient inputs (fertilizer) and outputs (harvested grains) from the soil during the experiment, and on (ii) changes in soil K availability up to a depth of 1.0 m. The initial content of 1.30 and 0.75 mmol dm–3 of exchangeable K in the soil medium and clay texture was enough to achieve higher productivity soybeans at 90% of maximum yield in the first three to four years of cultivation, respectively, no need to fertilize with K because the contribution of non-exchangeable K. The crop response to potassium fertilization increased, as the succeeding crops, and this increase corresponded to a decrease in soil nutrient reserves available. The annual application of 80 and 40 kg ha–1 K2O was sufficient to meet crop demand and maintain a constant level of exchangeable K in the soil of clayey and silty , respectively texture. Increasing the dose of potassium fertilizer intensified K losses by leaching the soil of medium texture, which ranged 4-78 kg ha–1 ...